The Relationship between Female Students Knowledge and Self-Breast Examination (SADARI) in Early Detection of Breast Cancer - Alfonsa Ivoni Larys Seran; Otniel Blegur; Ellyani Stevi Dwiputri Manafe (LPPM STIKes Muhammadiyah Ciamis, 2022)
Background: Cancer represents a collection of non-infectious ailments distinguished by the abnormal and malignant growth of cells or body tissues. Internationally, cancer remains a significant contributor to mortality and poses an ongoing challenge to national healthcare systems. Notably, breast cancer stands out as the predominant form of cancer among females, although, in certain instances, it can also manifest in males. Objective: To assess the level of awareness among female students about identifying early signs of breast cancer at State Vocational School 8 Kupang. Research methods: This study employed a quantitative research design, utilizing an analytic observational research method with a cross-sectional approach. The total sample size was 50, selected through a total sampling technique. Results: The analysis revealed that among the 50 respondents, 24 (48%) exhibited a low level of knowledge, and 29 (58%) were unable to perform breast self-examination. The Wilcoxon test yielded a significant value of 0.000 Conclusion: The findings suggest a correlation between students' knowledge and their ability to conduct breast self-examination (BSE) for the early detection of breast cancer at State Vocational School 8 Kupang.